HUBUNGAN HARGA DIRI DENGAN KECEMASAN MEMILIH PASANGAN HIDUP PADA PEREMPUAN DEWASA AWAL - Vania Utami; Lukmanul Hakim; Junaidin (JURNAL PSIMAWA, 2019)
This research aims to know the relationship between self-esteem and anxiety in choosing a spouse in early adult women.This research used quantitative descriptive approach. The technique of taking sampling is purposive sampling. Withdrawing sampling used Slovin formula, the sample of this research is fifty five early adult woman who are not married which is in the Kerato Village. The data of the research was carried out by using instrumental research called self-esteem and anxiety. The instrumen of reliability test using validity constrast. The result of this research showed that there are posiive correlations between self-esteem and anxiety by value of c0-efficiency correlation 0,663 with p value = 0,000/p<0,05 which means the higher it is self-esteem so the better it is anxiety in choosing a spouse, and vice versa. The lower self-esteem so the lower anxiety in choosing a spouse. Based on the research output, generally self-esteem be on high level and anxiety in choosing a spouse be on hight level.